Globalization and the Concept of Subsistence Wages - Block, Walter; Dauterive, Jerry; Levendis, John (Journal of Income Distribution®, 2007)
According to Malthus, there is an “Iron Law” for wages: they cannot stay above subsistence levels. When they do, increased population soon enough pushes them down to the previous level of immiseration. One might think that modern economics has long ago confined such views to the dustbin of history, however, belief in the “Iron Law” has made a comeback in this era of globalization. We argue that all versions of the Iron Law, new and old, are vulnerable to a knock-out critique. We argue that the Iron Law of Wages, and slavery for production and profit, are logically incompatible: if one ever existed, the other cannot.